2017
DOI: 10.21037/jtd.2017.04.37
|View full text |Cite
|
Sign up to set email alerts
|

Decrease in performance status after lobectomy mean poor prognosis in elderly lung cancer patients

Abstract: Background: Surgery remains the best treatment for obtaining cure in patients with resectable lung cancer, regardless of age. In elderly patients, however, the presumed fear of decreased performance status (PS) after lobectomy has resulted in the delivery of sub-optimal cancer surgery. Surgical decision making for such patients would become easier if post-lobectomy survival benefits and changes in PS were well defined. Methods:We reviewed patients aged 75 years or older who received lobectomy for non-small cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 17 publications
0
8
0
Order By: Relevance
“…As reported by others, older patients receive adjuvant chemotehrapy less often than younger patients, in spite of a similar survival benefit [ 16 ]. Moreover, the role of PS [ 17 ] as well as nodal status [ 18 ] as important factors influencing the treatment decision in patients with resectable NSCLC is well known.…”
Section: Discussionmentioning
confidence: 99%
“…As reported by others, older patients receive adjuvant chemotehrapy less often than younger patients, in spite of a similar survival benefit [ 16 ]. Moreover, the role of PS [ 17 ] as well as nodal status [ 18 ] as important factors influencing the treatment decision in patients with resectable NSCLC is well known.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with sarcopenia tend to have postoperative complications. The incidence of these complications may strongly predict a poor prognosis because physical ability is decreased by complications, resulting in poor responses to treatment for not only cancer but also other diseases (18). Third, a tumor occurring in sarcopenia patients has a more malignant potential than that occurring in patients without sarcopenia.…”
Section: Sarcopenia and Prognosismentioning
confidence: 99%
“…Compared with other tumors, the incidence and mortality of lung cancer are higher [ 3 ]. At the same time, the treatment of lung cancer still suffered great challenges on account of the metastasis and poor prognosis [ 23 , 24 ]. It is revealed that aberrant expression of transcriptional regulatory genes is closely associated with the emergence and malignant behavior of numerous cancers [ 25 , 26 ].…”
Section: Discussionmentioning
confidence: 99%